The Influence of Organizational Culture and Transformational Leadership on South Sulawesi Provincial Education Office Employees' Work Behavior - Andi Parianti; Hj. A. Ratna Sari Dewi (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to examine how organizational culture and transformational leadership affect employee work behavior at the South Sulawesi Province's education office. The study employed a quantitative survey methodology, and the data sample came from a survey given to the South Sulawesi Provincial Education Office workers. Equation models for linear regression were used to examine the data. According to the findings, organizational culture and transformational leadership both significantly influenced how South Sulawesi Provincial Education Office personnel behaved at work.